A method for preparing a porous adsorption material for adsorbing chloride ions and lead ions

By introducing porous structure and surface modification into hydrotalcite and combining grafting reaction of carboxytriazolyl starch, the problem of insufficient performance of existing adsorbent materials when treating wastewater containing chloride and lead ions is solved, and a more efficient adsorption effect is achieved.

CN119346082BActive Publication Date: 2025-03-11SHANDONG LIANGPU BUILDING MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411896054.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

When existing adsorption materials treat wastewater containing chloride and lead ions, it is difficult to effectively improve the specific surface area of ​​hydrotalcite and the adsorption performance of lead ions.

Method used

Porous magnesium-aluminum hydrotalcite is formed by adding sulfonated polystyrene microspheres, magnesium nitrate and aluminum nitrate to the water, followed by sodium hydroxide and sodium carbonate solutions, and after heating and calcination, porous magnesium-aluminum hydrotalcite is formed. Then, the porous magnesium-aluminum hydrotalcite is surface modified by KH560 and grafted with carboxytriazolyl starch to improve its adsorption performance.

Benefits of technology

The pore volume and specific surface area of ​​magnesium-aluminum hydrotalcite are significantly improved, and its adsorption performance and removal rate on chloride and lead ions are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to the technical field of adsorption materials, and discloses a method for preparing a porous adsorption material for adsorbing chloride ions and lead ions. KH560 modified porous magnesium aluminum hydrotalcite and carboxyl triazole starch are reacted to obtain a porous adsorption material for adsorbing chloride ions and lead ions. The invention grafts carboxyl triazole starch onto the surface of magnesium aluminum hydrotalcite, utilizes the coordination and chelation effect of carboxyl triazole structure on lead ions, and the flocculation and adsorption effect of starch molecular chain, and significantly improves the adsorption performance and removal rate of lead ions by magnesium aluminum hydrotalcite. After the magnesium aluminum hydrotalcite is grafted and modified, its dispersibility becomes better, agglomeration is reduced, and it has more adsorption sites. At the same time, the magnesium aluminum hydrotalcite has a large pore volume and a high specific surface area, and exhibits good adsorption performance and removal rate for chloride ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a method for preparing a porous adsorption material for adsorbing chloride ions and lead ions. Background Art

[0002] In the actual production process of electroplating, metallurgy, thermal power generation and other industries, a large amount of wastewater containing metal ions, chloride ion pollutants and other pollutants will be generated. These metal ion pollutants are difficult to degrade and are very harmful to human health and the growth and reproduction of plants and animals. Chloride ions will not only corrode pipes, but also form complexes with cations in water when discharged into surface water, seriously polluting surface water and the ecological environment. Therefore, it is urgent to remove metal ions, chloride ions and other pollutants in wastewater. Common adsorption materials for wastewater treatment include natural minerals, activated carbon, starch flocculants, triazole resins, etc.

[0003] Hydrotalcite is a layered double hydroxide, such as magnesium aluminum hydrotalcite, aluminum zinc hydrotalcite, etc., which can exchange with anions and has broad application prospects in the treatment of wastewater containing anionic pollutants. Patent CN115569640B discloses a method for preparing an adsorption treatment agent for phenol and chloride ions in coal chemical wastewater, using phenol as a template molecule, acrylamide, ethylene glycol dimethacrylate, modified polylactic acid, Zn / Al hydrotalcite, etc. as raw materials, and obtaining phenol molecular imprinting polymer microspheres through precipitation polymerization, which can effectively identify and adsorb phenol pollutants and trace chloride ion pollutants. However, the patent does not increase the specific surface area of ​​hydrotalcite, and the polymer microspheres do not show good adsorption performance for metal ions such as lead. Summary of the invention

[0004] (I) Technical problem to be solved: The present invention provides a porous hydrotalcite adsorption material that can adsorb chloride ions and metal ions.

[0005] (II) Technical solution: A method for preparing a porous adsorption material for adsorbing chloride ions and lead ions:

[0006] (1) Add sulfonated polystyrene microspheres to water, stir and then add magnesium nitrate and aluminum nitrate, stir and disperse for 2-4 hours, then drop an aqueous solution containing sodium hydroxide and sodium carbonate into the solution, then heat to 60-70°C, age for 18-24 hours, filter and wash with water, dry the product, place it in a muffle furnace, heat to 500-600°C, and calcine for 2-3 hours to obtain porous magnesium aluminum hydrotalcite.

[0007] (2) Add ethanol and porous magnesium aluminum hydrotalcite to water, stir and then add KH560, add glacial acetic acid dropwise to adjust the pH of the solution to 4-5, stir and react at 20-35°C for 3-8h, filter, wash with water and ethanol in turn, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite.

[0008] (3) Add KH560 modified porous magnesium aluminum hydrotalcite and carboxytriazole starch in a ratio of 1 g: (0.1-0.6) g to dimethyl sulfoxide, heat to 80-110°C, stir to react for 12-24 hours, filter, wash with dimethyl sulfoxide and water in turn, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0009] Furthermore, in (1), the ratio of sulfonated polystyrene microspheres, magnesium nitrate, aluminum nitrate, sodium hydroxide, and sodium carbonate is (150-400) g: 2 mol: 1 mol: (6-8) mol: (0.08-0.1) mol.

[0010] Furthermore, the ratio of porous Mg-Al-hydrotalcite and KH560 in (2) is 1 g: (0.04-0.08) g.

[0011] Furthermore, the preparation method of sulfonated polystyrene microspheres is as follows: add polystyrene microspheres to concentrated sulfuric acid, heat to 60-75°C, react for 4-7 hours, centrifuge, add the product to sodium hydroxide solution, stir for 1-2 hours, centrifuge, wash with ethanol aqueous solution, and dry to obtain sulfonated polystyrene microspheres.

[0012] Furthermore, the preparation method of carboxytriazole starch is as follows: add sulfuric acid solution to water and sodium periodate, stir, then add starch aqueous solution, stir and react at 30-35°C in the dark for 2-4 hours, filter, wash with water and ethanol in turn, and dry to obtain aldehyde starch.

[0013] Add aldehyde starch to dimethyl sulfoxide, add 5-carboxy-3-amino-1,2,4-triazole after stirring, add glacial acetic acid dropwise to adjust the solution pH to 4.5-5, raise the temperature to 50-60°C in a nitrogen atmosphere, stir and react for 4-6 hours, add ethanol to the solution for precipitation, filter, wash with ethanol, and dry to obtain carboxytriazole starch. The reaction formula is:

[0014] .

[0015] Furthermore, the ratio of aldehyde starch to 5-carboxy-3-amino-1,2,4-triazole is 1 g: (1.6-2.2) g.

[0016] (III) Technical effect: The present invention uses aluminum nitrate and magnesium nitrate as raw materials and sulfonated polystyrene microspheres as template agents. The sulfonate groups contained in the present invention can coordinate with magnesium and aluminum ions, thereby uniformly coating the magnesium and aluminum ions on the surface of the sulfonated polystyrene microspheres, reducing the agglomeration of the hydrotalcite precursor, and removing the polystyrene microsphere templates through high-temperature calcination to form a uniformly distributed porous structure in the hydrotalcite matrix, thereby increasing the pore volume and specific surface area of ​​the magnesium-aluminum hydrotalcite, which is beneficial to increasing the adsorption sites and adsorption performance of the magnesium-aluminum hydrotalcite.

[0017] The present invention utilizes KH560 to perform surface modification on porous magnesium aluminum hydrotalcite, and the introduced epoxy group reacts with the carboxyl group of carboxytriazole starch and the imino group of triazole at high temperature, so that the carboxytriazole starch is grafted onto the surface of magnesium aluminum hydrotalcite, and the coordination and chelation effect of the carboxytriazole structure on lead ions and the flocculation and adsorption effect of the starch molecular chain are utilized, thereby significantly improving the adsorption performance and removal rate of the magnesium aluminum hydrotalcite on lead ions.

[0018] After the magnesium aluminum hydrotalcite of the present invention is grafted and modified, its dispersibility is improved, agglomeration is reduced, and there are more adsorption sites. At the same time, the magnesium aluminum hydrotalcite has a large pore volume and a high specific surface area, and exhibits good adsorption performance and removal rate for chloride ions. DETAILED DESCRIPTION

[0019] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0020] The polystyrene microspheres of the present invention have an average particle diameter of 20 nm and are produced by Beijing Zhongke Keyou Technology Co., Ltd.

[0021] Embodiment 1:

[0022] (1) Add 10 g of polystyrene microspheres to 150 mL of 98% concentrated sulfuric acid, heat to 75°C, react for 4 h, centrifuge, add the product to 10% sodium hydroxide solution, stir for 1 h, centrifuge, wash with 80% ethanol aqueous solution, and dry to obtain sulfonated polystyrene microspheres.

[0023] (2) Add 20 mL of water and 8 g of sodium periodate, stir, add sulfuric acid solution to adjust the pH to 3, then add 30 mL of aqueous solution containing 5 g of starch, stir and react at 35 °C in a dark place for 2 h, filter, wash with water and ethanol in turn, and dry to obtain aldehyde starch.

[0024] (3) Add 7.5 g of sulfonated polystyrene microspheres to 200 mL of water, stir, add 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate, stir and disperse for 2 h, then add an aqueous solution containing 300 mmol of sodium hydroxide and 45 mmol of sodium carbonate to the solution, adjust the pH of the solution to 10, then heat to 65 °C, age for 24 h, filter and wash with water, dry the product, place it in a muffle furnace, heat to 600 °C, and calcine for 2 h to obtain porous magnesium aluminum hydrotalcite.

[0025] (4) Add 20 mL of ethanol and 20 g of porous magnesium aluminum hydrotalcite to 200 mL of water, stir, add 0.8 g of KH560, add glacial acetic acid dropwise to adjust the pH of the solution to 4, stir and react at 25 °C for 3 h, filter, wash with water and ethanol in turn, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite.

[0026] (5) Add 3 g of aldehyde starch to 50 mL of dimethyl sulfoxide, stir, then add 4.8 g of 5-carboxy-3-amino-1,2,4-triazole, add glacial acetic acid dropwise to adjust the pH of the solution to 4.5, raise the temperature to 60 °C in a nitrogen atmosphere, stir and react for 5 h, add ethanol to the solution for precipitation, filter, wash with ethanol, and dry to obtain carboxytriazole starch.

[0027] (6) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite and 2 g of carboxytriazole starch to 500 mL of dimethyl sulfoxide, heat to 80 °C, stir and react for 12 h, filter, wash with dimethyl sulfoxide and water in sequence, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0028] Embodiment 2:

[0029] (1) Add 10 g of polystyrene microspheres to 150 mL of 98% concentrated sulfuric acid, heat to 60°C, react for 7 h, and centrifuge. Add the product to 10% sodium hydroxide solution, stir for 2 h, centrifuge, wash with 80% ethanol aqueous solution, and dry to obtain sulfonated polystyrene microspheres.

[0030] (2) Add 30 mL of water and 13 g of sodium periodate, stir, add sulfuric acid solution to adjust the pH to 3, then add 40 mL of aqueous solution containing 5 g of starch, stir and react at 30 ° C in a dark place for 4 h, filter, wash with water and ethanol in turn, and dry to obtain aldehyde starch.

[0031] (3) Add 12 g of sulfonated polystyrene microspheres to 200 mL of water, stir, add 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate, stir and disperse for 4 h, then add an aqueous solution containing 400 mmol of sodium hydroxide and 50 mmol of sodium carbonate, adjust the pH of the solution to 9, then heat to 60 °C, age for 24 h, filter and wash with water, dry the product, place it in a muffle furnace, heat to 500 °C, and calcine for 3 h to obtain porous magnesium aluminum hydrotalcite.

[0032] (4) Add 20 mL of ethanol and 20 g of porous magnesium aluminum hydrotalcite to 200 mL of water, stir, add 1 g of KH560, add glacial acetic acid dropwise to adjust the pH of the solution to 5, stir and react at 35 °C for 3 h, filter, wash with water and ethanol in turn, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite.

[0033] (5) Add 3 g of aldehyde starch to 50 mL of dimethyl sulfoxide, stir, then add 5.3 g of 5-carboxy-3-amino-1,2,4-triazole, add glacial acetic acid dropwise to adjust the pH of the solution to 4.5, raise the temperature to 60 °C in a nitrogen atmosphere, stir and react for 4 h, add ethanol to the solution for precipitation, filter, wash with ethanol, and dry to obtain carboxytriazole starch.

[0034] (6) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite and 5 g of carboxytriazole starch to 600 mL of dimethyl sulfoxide, heat to 110 °C, stir and react for 12 h, filter, wash with dimethyl sulfoxide and water in sequence, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0035] Embodiment 3:

[0036] (1) 16 g of sulfonated polystyrene microspheres (prepared in Example 1) were added to 200 mL of water, and after stirring, 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate were added, and the mixture was stirred and dispersed for 4 h. Then, an aqueous solution containing 350 mmol of sodium hydroxide and 45 mmol of sodium carbonate was added dropwise to the solution, and the pH of the solution was adjusted to 10. The solution was then heated to 60° C. and aged for 24 h. After filtering, the solution was washed with water. After drying, the product was placed in a muffle furnace, heated to 550° C., and calcined for 3 h to obtain a porous magnesium aluminum hydrotalcite.

[0037] (2) Add 30 mL of ethanol and 20 g of porous magnesium aluminum hydrotalcite to 300 mL of water, stir, add 1.3 g of KH560, add glacial acetic acid dropwise to adjust the pH of the solution to 4, stir and react at 20 °C for 8 h, filter, wash with water and ethanol in turn, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite.

[0038] (3) 3 g of aldehyde starch (prepared in Example 1) was added to 50 mL of dimethyl sulfoxide. After stirring, 6 g of 5-carboxy-3-amino-1,2,4-triazole was added. Glacial acetic acid was added dropwise to adjust the pH of the solution to 5. The temperature was raised to 50° C. in a nitrogen atmosphere. The mixture was stirred for 6 h. Ethanol was added to the solution for precipitation. The solution was filtered, washed with ethanol, and dried to obtain carboxytriazole starch.

[0039] (4) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite and 9 g of carboxytriazole starch to 800 mL of dimethyl sulfoxide, raise the temperature to 80 °C, stir and react for 24 h, filter, wash with dimethyl sulfoxide and water in sequence, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0040] Embodiment 4:

[0041] (1) 20 g of sulfonated polystyrene microspheres (prepared in Example 1) were added to 200 mL of water, and after stirring, 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate were added, and the mixture was stirred and dispersed for 2 h. Then, an aqueous solution containing 400 mmol of sodium hydroxide and 40 mmol of sodium carbonate was added dropwise to the solution, and the pH of the solution was adjusted to 9. The solution was then heated to 70° C. and aged for 18 h. After filtering, the solution was washed with water, and the dried product was placed in a muffle furnace, heated to 600° C., and calcined for 2 h to obtain a porous magnesium aluminum hydrotalcite.

[0042] (2) Add 30 mL of ethanol and 20 g of porous magnesium aluminum hydrotalcite to 300 mL of water, stir, add 1.6 g of KH560, add glacial acetic acid dropwise to adjust the pH of the solution to 4, stir and react at 25 °C for 6 h, filter, wash with water and ethanol in turn, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite.

[0043] (3) 3 g of aldehyde starch (prepared in Example 1) was added to 50 mL of dimethyl sulfoxide. After stirring, 6.6 g of 5-carboxy-3-amino-1,2,4-triazole was added. Glacial acetic acid was added dropwise to adjust the pH of the solution to 4.5. The temperature was raised to 55° C. in a nitrogen atmosphere. The mixture was stirred for 6 h. Ethanol was added to the solution for precipitation. The solution was filtered, washed with ethanol, and dried to obtain carboxytriazole starch.

[0044] (4) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite and 12 g of carboxytriazole starch to 800 mL of dimethyl sulfoxide, raise the temperature to 90 °C, stir and react for 18 h, filter, wash with dimethyl sulfoxide and water in sequence, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0045] Comparative Example 1:

[0046] (1) Add 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate to 200 mL of water, stir and disperse for 2 h, then dropwise add an aqueous solution containing 300 mmol of sodium hydroxide and 45 mmol of sodium carbonate to the solution, adjust the pH of the solution to 10, then heat to 65 °C, age for 24 h, filter and wash with water, dry the product, place it in a muffle furnace, heat to 600 °C, and calcine for 2 h to obtain porous magnesium aluminum hydrotalcite.

[0047] Comparative Example 2:

[0048] (1) Add 7.5 g of polystyrene microspheres to 200 mL of water, stir, add 100 mmol of magnesium nitrate and 50 mmol of aluminum nitrate, stir and disperse for 2 h, then add an aqueous solution containing 300 mmol of sodium hydroxide and 45 mmol of sodium carbonate, adjust the pH of the solution to 10, then heat to 65 °C, age for 24 h, filter and wash with water, dry the product, place it in a muffle furnace, heat to 600 °C, and calcine for 2 h to obtain porous magnesium aluminum hydrotalcite.

[0049] The specific surface area of ​​the porous magnesium-aluminum hydrotalcite was tested by nitrogen adsorption and desorption using a physical adsorption instrument. Before the test, the porous magnesium-aluminum hydrotalcite was degassed at 100°C under vacuum for 24 hours.

[0050] Table 1

[0051]

[0052] After testing, the magnesium aluminum hydrotalcite of comparative example 1 did not have the template agent polystyrene microspheres added, and the total pore volume of the magnesium aluminum hydrotalcite was small, and the specific surface area was low.

[0053] In Example 1-4, sulfonated polystyrene microspheres are added as template agents, which contain sulfonate groups and can coordinate with magnesium and aluminum ions, thereby uniformly coating the magnesium and aluminum ions on the surface of the sulfonated polystyrene microspheres, reducing the agglomeration of the hydrotalcite precursor, and removing the polystyrene microsphere template after high-temperature calcination to form a uniformly distributed porous structure in the hydrotalcite matrix, so that the magnesium-aluminum hydrotalcite exhibits a higher pore volume and specific surface area.

[0054] The polystyrene microsphere template added in Comparative Example 2 does not contain sulfonate groups and cannot coordinate with magnesium and aluminum ions, making it difficult to evenly coat the magnesium and aluminum ions on the surface of the sulfonated polystyrene microspheres. The generated hydrotalcite precursor is easy to agglomerate, and the pore volume and specific surface area of ​​the magnesium-aluminum hydrotalcite after high-temperature calcination are significantly lower than those of Examples 1-4.

[0055] Comparative Example 3 uses porous magnesium-aluminum hydrotalcite as the porous adsorption material and is prepared according to Example 1.

[0056] Comparative Example 4 uses KH560 modified porous magnesium aluminum hydrotalcite as the porous adsorption material, which is prepared according to Example 1.

[0057] Comparative Example 5:

[0058] (1) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite, 2 g of starch, 0.12 g of sodium hydroxide, and 5 mL of water to 500 mL of dimethyl sulfoxide, heat to 80 °C, stir and react for 12 h, filter, wash with dimethyl sulfoxide and water in turn, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0059] Comparative Example 6:

[0060] (1) Add 20 g of KH560 modified porous magnesium aluminum hydrotalcite and 2 g of 5-carboxy-3-amino-1,2,4-triazole to 500 mL of dimethyl sulfoxide, heat to 80 °C, stir and react for 12 h, filter, wash with dimethyl sulfoxide and water in sequence, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions.

[0061] Add sodium chloride to 500 mL of water to control Cl - The mass concentration of 0.5g / L was added with 0.5-2g of porous adsorption material, stirred at 25℃ for 4h, and Cl was determined by spectrophotometry. - The removal rate was calculated based on the concentration.

[0062] Removal rate = (C0-C) / C0×100%. C0 is the Cl in the solution before adsorption. - C is the concentration of Cl in the solution after adsorption. - concentration.

[0063] Table 2

[0064]

[0065] Add lead nitrate to 500 mL of water to control Pb 2+ The mass concentration of Pb was 0.2 g / L, 1-3 g of porous adsorption material was added, stirred at 25 °C for 3 h, and the Pb 2+ The removal rate was calculated based on the concentration.

[0066] Removal rate = (C0-C) / C0×100%. C0 is the Pb content in the solution before adsorption. 2+ C is the concentration of Pb in the solution after adsorption. 2+ concentration.

[0067]

[0068] After testing, the porous magnesium aluminum hydrotalcites of Comparative Examples 1 and 2 have lower pore volumes, smaller specific surface areas, lower adsorption performance and removal rates for chloride ions, and fewer chemical functional groups on the surface of magnesium aluminum hydrotalcites, which have lower adsorption performance for Pb 2+ The adsorption performance is poor and the removal rate is low.

[0069] Comparative Example 3 uses porous magnesium-aluminum hydrotalcite as the porous adsorption material, which has large pore volume and specific surface area. Comparative Example 4 uses KH560 modified porous magnesium-aluminum hydrotalcite as the porous adsorption material. Both have significantly improved adsorption performance for chloride ions and lead ions, and the removal rate is higher than that of Comparative Example 1 and Comparative Example 2.

[0070] In Example 1-4, carboxytriazole starch was reacted with KH560 grafted magnesium aluminum hydrotalcite to graft starch molecular chains containing carboxytriazole structures onto the surface of magnesium aluminum hydrotalcite, and the coordination and chelation effect of carboxytriazole structures on lead ions and the flocculation and adsorption effect of starch molecular chains were utilized to significantly improve the adsorption performance and removal rate of lead ions by magnesium aluminum hydrotalcite. After grafting modification, the dispersibility of magnesium aluminum hydrotalcite became better, agglomeration was reduced, more adsorption sites were shown, and the removal rate of chloride ions was also improved to a certain extent.

[0071] In Comparative Example 5, sodium hydroxide was used as a catalyst to react the epoxy groups of porous magnesium-aluminum hydrotalcite modified by KH560 with the hydroxyl groups of starch; in Comparative Example 6, the epoxy groups of porous magnesium-aluminum hydrotalcite modified by KH560 were reacted with the amino groups of 5-carboxyl-3-amino-1,2,4-triazole. The adsorption performance of the porous adsorption materials obtained by the two for lead ions was significantly lower than that of Examples 1-4.

[0072] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A method for preparing a porous adsorbent material for adsorbing chloride ions and lead ions, characterized in that: The preparation method comprises the following steps: (1) Add sulfonated polystyrene microspheres to water, stir and then add magnesium nitrate and aluminum nitrate, stir and disperse, then drop an aqueous solution containing sodium hydroxide and sodium carbonate into the solution, then heat and age, filter and wash, dry and place the product in a muffle furnace for calcination to obtain porous magnesium aluminum hydrotalcite; (2) Add ethanol and porous magnesium aluminum hydrotalcite to water, stir, add KH560, drop glacial acetic acid, stir for reaction, filter, wash, and dry to obtain KH560 modified porous magnesium aluminum hydrotalcite; (3) Add aldehyde starch to dimethyl sulfoxide, add 5-carboxy-3-amino-1,2,4-triazole after stirring, add glacial acetic acid dropwise, stir and react in a nitrogen atmosphere, add ethanol to the solution for precipitation, filter, wash, and dry to obtain carboxytriazole starch; (4) Add KH560 modified porous magnesium aluminum hydrotalcite and carboxyl triazole starch in a ratio of 1 g: (0.1-0.6) g to dimethyl sulfoxide, stir and react at 80-110° C. for 12-24 hours, filter, wash, and dry to obtain a porous adsorption material for adsorbing chloride ions and lead ions; The ratio of sulfonated polystyrene microspheres, magnesium nitrate, aluminum nitrate, sodium hydroxide and sodium carbonate in (1) is (150-400) g: 2 mol: 1 mol: (6-8) mol: (0.08-0.1) mol; The ratio of porous magnesium aluminum hydrotalcite and KH560 in (2) is 1g: (0.04-0.08)g; Add glacial acetic acid to adjust the solution pH to 4-5; The ratio of aldehyde starch to 5-carboxyl-3-amino-1,2,4-triazole in (3) is 1 g: (1.6-2.2) g; glacial acetic acid is added dropwise to adjust the pH of the solution to 4.5-5; The reaction in (3) is carried out at 50-60° C. for 4-6 hours; The preparation method of the sulfonated polystyrene microspheres is as follows: adding polystyrene microspheres to concentrated sulfuric acid, heating to 60-75° C., reacting for 4-7 hours, centrifuging, adding the product to a sodium hydroxide solution, stirring for 1-2 hours, centrifuging, washing, and drying to obtain the sulfonated polystyrene microspheres.

2. The method for preparing a porous adsorbent material for adsorbing chloride ions and lead ions according to claim 1, characterized in that: The stirring and dispersing time in (1) is 2-4 hours; the aging temperature is 60-70°C and the time is 18-24 hours; the calcination temperature is 500-600°C and the time is 2-3 hours.

3. The method for preparing a porous adsorbent material for adsorbing chloride ions and lead ions according to claim 1, characterized in that: The reaction in (2) is carried out at 20-35°C for 3-8 hours.

4. The method for preparing a porous adsorbent material for adsorbing chloride ions and lead ions according to claim 1, characterized in that: The preparation method of the aldehyde starch is as follows: add sulfuric acid solution to water and sodium periodate, stir, then add starch aqueous solution, stir and react at 30-35° C. in the dark for 2-4 hours, filter, wash, and dry to obtain the aldehyde starch.

Citation Information

Patent Citations

  • A method for preparing a phenol adsorption agent for coal chemical wastewater

    CN115569640B

  • Sewage treatment method combining hydrotalcite adsorption pretreatment and biochemical treatment and integrated sewage treatment device thereof

    CN115159770A

  • Sorbent material

    EP2072117A1